Problem solving stages in the five square problem - Fedor, Anna; Szathmáry, Eörs; Öllinger, Michael (Frontiers in Psychology, 2015)
According to the restructuring hypothesis, insight problem solving typically progresses through consecutive stages of search, impasse, insight and search again for someone, who solves the task. The order of these stages was determined through self-reports of problem solvers and has never been verified behaviourally. We asked whether individual analysis of problem solving attempts of participants revealed the same order of problem solving stages as defined by the theory and whether their subjective feelings corresponded to the problem solving stages they were in. 101 participants tried to solve the Five-Square problem in an online task, while we recorded the time and trajectory of their stick movements. After the task they were asked about their feelings related to insight and 67 of them also had the possibility of reporting impasse while working on the task. We have found that 49% (19 out of 39) of the solvers and 13% (8 out of 62) of the non-solvers followed the classic four-stage model of insight. The rest of the participants had more complex sequences of problem solving stages, with search and impasse recurring several times. This means that the classic four-stage model must be extended to explain variability on the individual level. We provide a model that can generate all sequences found. Solvers reported insight more often than non-solvers and non-solvers reported impasse more often than solvers, as expected; but participants did not report impasse more often during behaviourally defined impasse stages than during other stages. This shows that impasse reports might be unreliable indicators of impasse. Our study highlights the importance of individual analysis of problem solving behaviour to verify insight theory.